ANALGESIC AND ANTI-LITHIASIC EFFECTS OF MOROCCAN Citrus aurantium FLOWERS AND FRUIT AQUEOUS EXTRACTS - Elyazouli loubna; Baslam Abdelmounaim; Laadraoui Jawad; Ait Laaradia Mehdi; Aboufatima Rachida; Moubtakir Souad; El Amiri My Ahmed; Kebou aziz; chait abderrahman (Journal of Animal and Plant Sciences, 2024)
Citrus aurantium holds widespread use in Moroccan society as a remedy for various diseases, owing to its significant pharmacological properties. The objective of this study was to investigate the antioxidant activity, analgesic potential, and anti-lithiasis properties of the aqueous extracts of both the fruits and juice of Citrus aurantium. To achieve this, we employed various techniques: antioxidant activity was assessed using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and reducing power assays (FRAP), while the antinociceptive effect of the plant was evaluated through writhing and hotplate tests on mice. The urolithiasis model was induced in rats through the administration of ethylene glycol and ammonium chloride, and assessments were made based on variations in body weight, kidney histopathology, and biochemical analysis using urea and creatinine. Our findings demonstrated significant antioxidant activity in both extracts (flowers and juice) of Citrus aurantium, represented by DPPH values of 5.42±0.20 and 2.87±0.42, and FRAP values of 4.23±0.05 and 1.67±0.13 in flowers and juice, respectively. The obtained results also showed that Citrus aurantium extracts significantly reduced the number of writhes and increased the latency time in response to a thermal stimulus compared to the control group (p≤0.001). Both extracts (flowers and juice) of Citrus aurantium exhibited a protective effect on the kidneys by preventing the formation of oxalo-calcium crystals. The histopathological study of the kidneys in the groups treated with Citrus aurantium revealed a marked reduction in abnormalities observed in rats treated with Ethylene Glycol. Additionally, urea and creatinine values were reduced compared to the control group (p≤0.001), signifying an important anti-urolithiasic activity. Overall, Citrus aurantium demonstrated potent antioxidant, analgesic and antilithic activities, suggesting its potential as a valuable natural source of bioactive compounds with various therapeutic applications.
Keywords: Citrus aurantium